The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/her/cyt037
|View full text |Cite
|
Sign up to set email alerts
|

Gang membership of California middle school students: behaviors and attitudes as mediators of school violence

Abstract: Empirical evidence examining how risk and protective behaviors may possibly mediate the association between gang membership and school violence is limited. This study utilizes a statewide representative sample of 152 023 Latino, Black and White seventh graders from California to examine a theoretical model of how school risk (e.g. truancy, school substance use and risky peer approval) and protective (e.g. connectedness, support and safety) behaviors and attitudes mediate the effects of gang membership on schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Children who experience relationships and environments that promote these factors, individually and in combination, are more likely to build healthy brain architecture and less likely to experience toxic stress in their environment (Conger, Schofield, Neppl, & Merrick, 2013; Dixon, Browne, & Hamilton-Giachritsis, 2009; Mercy & Saul, 2009; Shonkoff, Boyce, & McEwen, 2009). They also may be less likely to be victims and perpetrators of school violence (Estrada, Gilreath, Astor & Benbenishty, 2013; Hill et al, 1999), have higher emotional intelligence (Elipe, Del Rey, & Ortega-Ruiz, 2015) and higher academic achievement (Hurd & Sellers, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Children who experience relationships and environments that promote these factors, individually and in combination, are more likely to build healthy brain architecture and less likely to experience toxic stress in their environment (Conger, Schofield, Neppl, & Merrick, 2013; Dixon, Browne, & Hamilton-Giachritsis, 2009; Mercy & Saul, 2009; Shonkoff, Boyce, & McEwen, 2009). They also may be less likely to be victims and perpetrators of school violence (Estrada, Gilreath, Astor & Benbenishty, 2013; Hill et al, 1999), have higher emotional intelligence (Elipe, Del Rey, & Ortega-Ruiz, 2015) and higher academic achievement (Hurd & Sellers, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…School violence represents the extreme end of the safety continuum in the school ecology and there is ample evidence for its detrimental effects on developmental outcomes. School violence has been shown to be associated with other delinquent activities such as gang membership (Estrada, Gilreath, Astor & Benbenishty, 2013) and bullying (Bradshaw, Waasdorp, Debnam, & Johnson, 2014). Violence and aggressive behavior among school-aged youth have also been shown to negatively impact cognition, school connectedness, and school attendance, which have cumulative effects on academic achievement (Basch, 2011) and interpersonal relationships (Elipe, Del Rey, Ortega-Ruiz, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research [28,29] has identified perceived peer prejudice in school to be a factor related to negative experiences and behaviors in the school environment among adolescents including but not limited to unexcused absences and/or truancy, violence and aggression, and bullying [28][29][30].…”
Section: The Relationship Between Perceptions Of Peer Prejudice and Smentioning
confidence: 99%